Relationship between official performance measurement scores and Relative efficiency in general hospitals - Alireza Ilbeigi; Mostafa Kazemi; Mohammad Taghi Peivandi (Tehran University of Medical Sciences, 2012)
Background: The aim of this research was to measure and compare relative efficiency of general hospitals under supervision of Mashhad University of Medical Sciences (MUMS). The study also seek to investigate the likely relationship between the official evaluating scores reported by MUMS with findings of this study. Materials & Methods: Data Envelopment Analysis (DEA) is utilized to determine relative efficiency of individual decision making units (DMUs). From state-run general hospitals in this study, 17 were selected based on the criteria suggested by the model. To distinguish efficient hospitals from inefficient ones, revised input-based BCC model was used incorporating 'number of physicians' and 'number of nurses' as inputs. Outputs were set as 'the rate of inpatient days to staffed beds', 'outpatient visits' and 'number of surgeries' reported both at emergency and wards. Results: The findings based on both CRS and VRS simulations indicate that the mean of technical efficiency was 0.823, mean managerial efficiency was 0.931 and subsequently mean scale efficiency was 0.881. It was further noticed that, there was no significant relationship between the performance appraisal outcomes from DEA model, and scores allocated to each hospital through official evaluation system. Conclusion: Current official appraisal system based on pre-defined checklists may not be a reliable mean for evaluating and ranking efficiency of general hospitals.